A Note on the Taittirîya Manuscripts Belonging to the Van Manen Collection, Kern Institute, Leiden - Rath, Saraju (Acta Orientalia Vilnensia, 2005)
International Institute for Asian Studies, LeidenA collection of ca. 380 Sanskrit palm-leaf manuscript bundles, acquired from South India by the Dutch Orientalist Johan Van Manen between 1928–1931, is preserved in the library at Kern Institute, Leiden University. No catalogue is available for this collection. In my survey of this collection (June–November 2002), I focused on the manuscripts of the Taittirîya school of the Black-Yajurveda, one of the few Vedic ritual traditions that survived through numerous socio-religious changes over ca. two millennia and is currently still in practice in India. Twenty-three palm-leaf manuscripts with texts belonging to the Taittirîya tradition were selected for further study. In the present article, I briefly discuss my findings regarding the external condition of the manuscripts and the texts they contain.